2011
DOI: 10.1177/0892705711429982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triton X-100 on MWCNT/PP composites

Abstract: A nonionic surfactant, Triton X-100, was used to treat multiwalled carbon nanotubes (MWCNTs), and the Triton X-100-treated MWCNTs (TCNTs) were then mixed with polypropylene (PP) to prepare MWCNT/PP composites, followed by characterization using scanning electron microscopic, electrical, mechanical and thermal measurements. It was found that the best usage of Triton X-100 for the treatment of MWCNTs was 80 wt% based on the MWCNTs. The TCNTs could effectively improve the electrical conductivity and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…12 Our group recently studied the effect of a non-ionic surfactant, Triton X-100, as a dispersing aid, on the electrical, mechanical, and crystalline properties of MWCNT/ polypropylene (PP) composites. 13 We found that Triton X-100 is able to significantly decrease the percolation threshold for electrical conductivity to result in a higher electrical conductivity. 13 Silane coupling agents also have been used in some applications for surface modification of nanoparticles for improving dielectric properties in organic-inorganic nanocomposites.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…12 Our group recently studied the effect of a non-ionic surfactant, Triton X-100, as a dispersing aid, on the electrical, mechanical, and crystalline properties of MWCNT/ polypropylene (PP) composites. 13 We found that Triton X-100 is able to significantly decrease the percolation threshold for electrical conductivity to result in a higher electrical conductivity. 13 Silane coupling agents also have been used in some applications for surface modification of nanoparticles for improving dielectric properties in organic-inorganic nanocomposites.…”
Section: Introductionmentioning
confidence: 73%
“…13 We found that Triton X-100 is able to significantly decrease the percolation threshold for electrical conductivity to result in a higher electrical conductivity. 13 Silane coupling agents also have been used in some applications for surface modification of nanoparticles for improving dielectric properties in organic-inorganic nanocomposites. 14 Silane coupling agents are organosilicon compounds that have two different groups: one that reacts with a polymer matrix and the other that reacts with fillers such as CNTs.…”
Section: Introductionmentioning
confidence: 73%